2017
DOI: 10.1371/journal.pone.0188181
|View full text |Cite
|
Sign up to set email alerts
|

Single molecule sequencing of the M13 virus genome without amplification

Abstract: Next generation sequencing (NGS) has revolutionized life sciences research. However, GC bias and costly, time-intensive library preparation make NGS an ill fit for increasing sequencing demands in the clinic. A new class of third-generation sequencing platforms has arrived to meet this need, capable of directly measuring DNA and RNA sequences at the single-molecule level without amplification. Here, we use the new GenoCare single-molecule sequencing platform from Direct Genomics to sequence the genome of the M… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Third-generation sequencing was performed on the single-molecule sequencer GenoCare at the GeneMind Biosciences Company Limited, Guangzhou, China. GenoCare sequencing was performed according to a previously disclosed protocol [ 11 ]. We found that the two patients’ deletions were identical; both were 6.0 Mb, with breakpoints at 44850001 bp and 50,850,001 bp (GRCh37/hg19).…”
Section: Case Presentationmentioning
confidence: 99%
“…Third-generation sequencing was performed on the single-molecule sequencer GenoCare at the GeneMind Biosciences Company Limited, Guangzhou, China. GenoCare sequencing was performed according to a previously disclosed protocol [ 11 ]. We found that the two patients’ deletions were identical; both were 6.0 Mb, with breakpoints at 44850001 bp and 50,850,001 bp (GRCh37/hg19).…”
Section: Case Presentationmentioning
confidence: 99%
“…Recently, GeneMind Biosciences Company Limited (GeneMind), launched a new sequencing instrument (GenoLab M™) based on their previous work on Geno-Care™ single molecule sequencer [16]. An overview of the mechanism of GenoLab M DNA sequencer is outlined in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The samples were sequenced on Genemind Bioscience's single-molecule sequencer GenoCare and Illumina's HiseqX10 sequencer, yielding more than 4% genome coverage for each sample. GenoCare sequencing was performed according to the previously disclosed protocol [11]. For each sample, 25% of the area of each flowcell channel was imaged, and 72 cycles of sequencing data were collected, yielding more than 4 million reads.…”
Section: Sequencing and Data Analysismentioning
confidence: 99%